A Preliminary Study on the Impact of Digital Transformation on Enterprise Competitive Advantage - Xie, Yifei; Song, Zhenggang (Transactions on Economics, Business and Management Research, 2024)
With the rapid development of digital technologies such as big data and cloud computing, more and more enterprises are participating in the wave of digital transformation. Although many scholars have explored the impact of digital transformation on corporate performance, the improvement of performance does not mean that enterprises can gain a dominant position in market competition, and the relationship between digitization and corporate performance is complicated, and the relationship between the two is still controversial. Competitive advantage is the antecedent of performance. Focusing on competitive advantage research is not only conducive to further understanding the impact of digital transformation on enterprises, but also helpful to reveal the complex relationship between digital transformation and performance. On the basis of expounding the connotation of enterprise digital transformation and competitive advantage, this paper discusses the influence of enterprise digital transformation on the source of competitive advantage from two aspects: exogenous and endogenous, combined with industrial organization theory and resource-based theory. From the perspective of optimizing internal conditions, responding to external environment, adjusting competition and cooperation relationship, demand response and product innovation, this paper discusses the ways in which enterprises can gain competitive advantage through digital transformation.